A novel structural effector from rust fungi is capable of fibril formation. (10th June 2013) - Kemen, Eric; Kemen, Ariane; Ehlers, Andreas; Voegele, Ralf; Mendgen, Kurt
Summary: It has been reported that filament‐forming surface proteins such as hydrophobins are important virulence determinants in fungi and are secreted during pathogenesis. Such proteins have not yet been identified in obligate biotrophic pathogens such as rust fungi. Rust transferred protein 1 (RTP1p), a rust protein that is transferred into the host cytoplasm, accumulates around the haustorial complex. To investigate RTP1p structure and function, we used immunocytological, biochemical and computational approaches. We found that RTP1p accumulates in protuberances of the extra‐haustorial matrix, a compartment that surrounds the haustorium and is separated from the plant cytoplasm by a modified host plasma membrane. Our analyses show that RTP1p is capable of forming filamentous structures in vitro and in vivo . We present evidence that filament formation is due to β–aggregation similar to what has been observed for amyloid‐like proteins. Our findings reveal that RTP1p is a member of a new class of structural effectors. We hypothesize that RTP1p is transferred into the host to stabilize the host cell and protect the haustorium from degradation in later stages of the interaction. Thus, we provide evidence for transfer of an amyloid‐like protein into the host cell, which has potential for the development of new resistance mechanisms against rust fungi.